2016
DOI: 10.3389/fcimb.2016.00147
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Lipoprotein Rv1016c Derived from Mycobacterium tuberculosis Is a TLR-2 Ligand that Induces Macrophages Apoptosis and Inhibits MHC II Antigen Processing

Abstract: TLR2-dependent cellular signaling in Mycobacterium tuberculosis-infected macrophages causes apoptosis and inhibits class II major histocompatibility complex (MHC-II) molecules antigen processing, leading to evasion of surveillance. Mycobacterium tuberculosis (MTB) lipoproteins are an important class of Toll-like receptor (TLR) ligand, and identified as specific components that mediate these effects. In this study, we identified and characterized MTB lipoprotein Rv1016c (lpqT) as a cell wall associated-protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 49 publications
1
19
1
Order By: Relevance
“…176 It is worth mentioning that immune evasion via modulation of TLR2 by the recombinant lipoprotein Rv1016c, induces apoptosis of macrophages by increasing annexin expression. 177 Consequently, this relationship becomes beneficial because in addition to Rv1016c inhibition of MHC-II expression, TLR2-dependent apoptosis may promote the release of residual bacilli into apoptotic cells and, thereby, decrease the recognition of CD4+ T cells, impairing surveillance in chronic disease conditions (Figure 3). 177 Concerning protozoa, one of the main parasites that compromise macrophage activity is Leishmania.…”
Section: Mechanisms Of Immune Evasion Used By Intracellular Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…176 It is worth mentioning that immune evasion via modulation of TLR2 by the recombinant lipoprotein Rv1016c, induces apoptosis of macrophages by increasing annexin expression. 177 Consequently, this relationship becomes beneficial because in addition to Rv1016c inhibition of MHC-II expression, TLR2-dependent apoptosis may promote the release of residual bacilli into apoptotic cells and, thereby, decrease the recognition of CD4+ T cells, impairing surveillance in chronic disease conditions (Figure 3). 177 Concerning protozoa, one of the main parasites that compromise macrophage activity is Leishmania.…”
Section: Mechanisms Of Immune Evasion Used By Intracellular Pathogensmentioning
confidence: 99%
“…177 Consequently, this relationship becomes beneficial because in addition to Rv1016c inhibition of MHC-II expression, TLR2-dependent apoptosis may promote the release of residual bacilli into apoptotic cells and, thereby, decrease the recognition of CD4+ T cells, impairing surveillance in chronic disease conditions (Figure 3). 177 Concerning protozoa, one of the main parasites that compromise macrophage activity is Leishmania. 163 L. major negatively modulates TLR2 receptor activity to increase the recruitment of SOCS1 and SOCS3, which inhibit the production of NF-kB, IFN-γ, and TNF-α in order to establish pathogen survival.…”
Section: Mechanisms Of Immune Evasion Used By Intracellular Pathogensmentioning
confidence: 99%
“…LpqT could decrease the cleaved levels of caspase-3 by blocking the TLR-2 signaling pathway (Table 1) [39]. However, the previous study demonstrated that LpqT could increase the apoptosis of THP-1 macrophage and monocyte-derived macrophages (MDM) via agonist TLR-2 signaling [40]. Therefore, the exact role of Mtb LpqT in the regulation of macrophage apoptosis in the context of its interaction with TLR-2 remains controversial.…”
Section: Anti-apoptotic Determinants Of Mycobacteriummentioning
confidence: 99%
“…TLR2-Mtb lipoprotein interaction inhibits IFN-c-induced MHC-II expression and processing of soluble antigens in a Class II transactivator (CIITA) IVdependent and MAPK-dependent manner. 110 Repressed MHC-II expression and enhanced TLR2driven macrophage apoptosis decrease antigen recognition by CD4 + T cells. IL-10 plays a significant role in this process.…”
Section: Presentation Of the Processed Mycobacterial Antigens To T Cellsmentioning
confidence: 99%